82.0k views
5 votes
PLS HELP WILL GIVE 30 POINTS

PLS HELP WILL GIVE 30 POINTS-example-1
User Axlan
by
5.3k points

1 Answer

3 votes

Answer:
y=-(1)/(3) x^2 +(2)/(3)x+(26)/(3)

Explanation:

The equation in vertex form is
y=a(x-1)^2 +9.

Substituting in the coordinates (4,6) to solve for a,


6=a(4-1)^2 +9\\\\6=9a+9\\\\9a=-3\\\\a=-(1)/(3)\\\\

This means the equation in vertex form is
y=-(1)/(3)(x-1)^2 +9. Expanding this out into standard form,


y=-(1)/(3)(x^2 -2x+1)+9\\\\=-(1)/(3)x^2 +(2)/(3)x-(1)/(3)+9\\\\=-(1)/(3)x^2 +(2)/(3)x+(26)/(3)

User Sheh
by
5.0k points